Sintesis Nanotitania dengan Cara Hidrotermal sebagai Fungsi Suhu - Sumiyati Sumiyati; Posman Manurung; Suprihatin Suprihatin (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Research has been carried out on the synthesis of nanotitania by hydrothermal as a function of temperature. The purpose of this study was to determine the effect of temperature on the phase formation, structure and particle size of TiO2 using the hydrothermal method with TiOSO4 as the main ingredient. In this study, using temperature variations of 150, 200, 250 and 300°C and samples were characterized using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The phases formed are the anatase and rutile phases which have a tetragonal structure and the hilly phase with an orthorhombic structure. The rutile phase appeared predominantly in each sample and the sulfuric phase only appeared at 250ºC. The anatase phase obtains a particle size of 10-18 nm, where the higher the temperature, the bigger the particle size. Furthermore, the rutile phase obtained a particle size of 14-25 nm, where the higher the temperature, the smaller the particle size.